Perioperative Complications During Living Donor Nephrectomy: Results From a Multicenter Cohort Study. Issue 1 (July 2019) - Garcia-Ochoa, Carlos; Feldman, Liane S.; Nguan, Christopher; Monroy-Cuadros, Mauricio; Arnold, Jennifer; Boudville, Neil; Cuerden, Meaghan; Dipchand, Christine; Eng, Michael; Gill, John; Gourlay, William; Karpinski, Martin; et al.
Background: While living kidney donation is considered safe in healthy individuals, perioperative complications can occur due to several factors. Objective: We explored associations between the incidence of perioperative complications and donor characteristics, surgical technique, and surgeon's experience in a large contemporary cohort of living kidney donors. Design: Living kidney donors enrolled prospectively in a multicenter cohort study with some data collected retrospectively after enrollment was complete (eg, surgeon characteristics). Setting: Living kidney donor centers in Canada (n = 12) and Australia (n = 5). Patients: Living kidney donors who donated between 2004 and 2014 and the surgeons who performed the living kidney donor nephrectomies. Measurements: Operative and hospital discharge medical notes were collected prospectively, with data on perioperative (intraoperative and postoperative) information abstracted from notes after enrollment was complete. Complications were graded using the Clavien-Dindo system and further classified into minor and major. In 2016, surgeons who performed the nephrectomies were invited to fill an online survey on their training and experience. Methods: Multivariable logistic regression models with generalized estimating equations were used to compare perioperative complication rates between different groups of donors. The effect of surgeon characteristics on the complication rate was explored using a similar approach. Poisson regression was used to test rates of overall perioperative complications between high- and low-volume centers. Results: Of the 1421 living kidney donor candidates, 1042 individuals proceeded with donation, where 134 (13% [95% confidence interval (CI): 11%-15%]) experienced 142 perioperative complications (55 intraoperative; 87 postoperative). The most common intraoperative complication was organ injury and the most common postoperative complication was ileus. No donors died in the perioperative period. Most complications were minor (90% of 142 complications [95% CI: 86%-96%]); however, 12 donors (1% of 1042 [95% CI: 1%-2%]) experienced a major complication. No statistically significant differences were observed between donor groups and the rate of complications. A total of 43 of 48 eligible surgeons (90%) completed the online survey. Perioperative complication rates did not vary significantly by surgeon characteristics or by high- versus low-volume centers. Limitations: Operative and discharge reporting is not standardized and varies among surgeons. It is possible that some complications were missed. The online survey for surgeons was completed retrospectively, was based on self-report, and has not been validated. We had adequate statistical power only to detect large effects for factors associated with a higher risk of perioperative complications. Conclusions: This study confirms the safety of living kidney donation as evidenced by the low rate of major perioperative complications. We did not identify any donor or surgeon characteristics associated with a higher risk of perioperative complications. Trial registration(s): NCT00319579: A Prospective Study of Living Kidney Donation (https://clinicaltrials.gov/ct2/show/NCT00319579 ) NCT00936078: Living Kidney Donor Study (https://clinicaltrials.gov/ct2/show/NCT00936078 )